Multiple Episodes of Hemorrhage Identified in MRI of Chronic Subdural Hematomas - Seo, Dong-Ho (Korean J Neurotrauma, 2014)
OBJECTIVE: Septa within the hematoma cavity are common, especially in the mixed density chronic subdural hematomas (CSHs). Although CT remains the diagnosis of choice, MRI is superior to detect the membranes in CSHs. We could obtain MRIs in 64 patients with CSH. We examined the value of MRI to understand the history of CSH. METHODS: We retrospectively examined the medical records and MRIs of 64 consecutive patients. MRI was selected to find any organic causes of neurologic symptoms. We classified the CSHs into septated or non-septated group, since classification of the septa was frequently obscure. RESULTS: Septa were identified by MRI in 43 patients (67%). They were more common in the over 70-years-old group. Unknown causes were more common in the septated group, which implies they might suffer from multiple traumas. The signal intensity of the CSH was variable. The methods of treatment were different between two groups. Surgery was more common in the septated group (p=0.021). Surgery was performed in 57 patients (89%). Burr-hole drainage was successful in 55 patients, even in the septated group. CONCLUSION: Septa within the hematoma cavity may be related to the multiple episodes of head trauma. Repeated trauma may cause acute bleedings over the CSHs, which is one of the pathogenic mechanisms of hematoma enlargement. MRI could show the history of CSH.